A Population on the Brink: American Renters, Emergency Savings, and Financial Fragility. Issue 1 (March 2016) - West, Stacia; Mottola, Gary
Abstract: Financial fragility and inadequate emergency savings are commonly associated with lower educational attainment, lower household income, younger age, minority status, and lower rates of financial knowledge and financial literacy. Using the 2012 National Financial Capability Study ( N = 25, 509), the purpose of this research was to determine if renters, compared to homeowners, were more likely to report financial fragility or inadequate emergency savings. Results of logistic regressions suggest that renters were 75 percent more likely to experience financial fragility and 93 percent more likely to lack adequate emergency savings than homeowners. Considered in tandem with other research on the outcomes of financial fragility, these findings suggest that renters, if confronted with an income or expenditure shock, may not be able to draw upon existing resources and may be at risk for housing instability.